Adult and Pediatric Neuromodulation (Springer International Publishing, 2018)
This text reviews the anatomy and physiology of neuromodulation for treatment of various pathology of the human body, with specific emphasis on sacral neuromodulation for bladder and bowel dysfunction in the adult and pediatric populations. In addition to historical overview of the various methods of neuromodulation, present day applications will be discussed as well as possible future directions for use. Adult and Pediatric Neuromodulation will be of great value to medical professionals who are interested in the use of neuromodulation as a possible therapy option for their patients, particularly when other traditional or medical management options have failed. Each chapter is written by experts in the topic of various modalities of neuromodulation.